2017
DOI: 10.1536/ihj.16-556
|View full text |Cite
|
Sign up to set email alerts
|

Change of Exhaled Acetone Concentration in a Diabetic Patient with Acute Decompensated Heart Failure

Abstract: SummaryIn heart failure patients, exhaled acetone concentration, a noninvasive biomarker, is increased according to heart failure severity. Moreover, exhaled acetone concentration is also known to be affected by diabetes mellitus. However, there have been no reports on exhaled acetone concentration in heart failure patients with diabetes mellitus. A 77-year old man was admitted to our hospital with acute decompensated heart failure and atrioventricular block. He had controlled diabetes mellitus under insulin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This study also confirms that changes in exhaled levels of acetone and pentane correlate with changes in disease severity of ADHF patients, as suggested by several previous reports [2][3][4][5][6][7][8][11][12][13] and demonstrates the feasibility of using single exhaled breath samples for risk stratification in ADHF. A recently pilot CPET study in HF patients also showed increased breath levels of acetone and pentane at rest using SIFT-MS technology [2].…”
Section: Exhaled Acetone and Pentane In Heart Failuresupporting
confidence: 90%
See 1 more Smart Citation
“…This study also confirms that changes in exhaled levels of acetone and pentane correlate with changes in disease severity of ADHF patients, as suggested by several previous reports [2][3][4][5][6][7][8][11][12][13] and demonstrates the feasibility of using single exhaled breath samples for risk stratification in ADHF. A recently pilot CPET study in HF patients also showed increased breath levels of acetone and pentane at rest using SIFT-MS technology [2].…”
Section: Exhaled Acetone and Pentane In Heart Failuresupporting
confidence: 90%
“…Several studies have identified elevated levels of nitric oxide, pentane, and acetone in the exhaled breath in patients with CHF [1][2][3][4][5]. Data published from our own group has also shown the feasibility of measuring inpatient breath VOC analysis using selected ion flow tube mass spectrometry (SIFT-HF) technology, and the ability of exhaled acetone and pentane to discriminate between patients with and without CHF [6][7][8]. However, most exhaled breath studies to date have been case-control, cross-sectional analyses, and few examined how patients' levels of exhaled VOCs correlate with their clinical changes or functional capacity.…”
Section: Introductionmentioning
confidence: 96%
“…Heart failure (HF) represents the final common pathway of different cardiac diseases and is a major cause of death among the elderly in many countries (1)(2)(3)(4). Currently, risk management and treatment of HF mainly depend on current left ventricular ejection fraction (LVEF) in clinical practice (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…H eart failure (HF) is a major cause of death among the elderly in many countries. [1][2][3][4] It has been recently reported that sleep disturbance is associated with an increased risk of incident cardiovascular disease (CVD) [5][6][7][8] and HF. 9,10) Restless legs syndrome (RLS) is a neurological disorder characterized by an irresistible urge to move the legs or arms for relief of uncomfortable or unpleasant sensations.…”
mentioning
confidence: 99%